Contemporary Role and Responsibilities of the Director of Clinical Education: A National Qualitative Study. Issue 4 (December 2018) - McCallum, Christine; Engelhard, Chalee; Applebaum, Donna; Teglia, Valerie
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Clinical education is of broad and current interest topic in physical therapist (PT) education today. The director of clinical education (DCE) is the core faculty member responsible for the components of the clinical education (CE) curriculum. Previous work has questioned whether the position would be a "dinosaur or a rising phoenix". The objectives of this study was to comprehensively examine the full scope of the role and responsibilities of the DCE. Methods: A non-experimental, qualitative descriptive study design was used. A constructivist theoretical framework guided the work. Eleven teams of DCEs and program directors (PD) participated in semi-structured interviews. Onsite interviews were conducted by trained interviewers and transcribed verbatim for analysis. A process of thematic analysis was used to develop results. Results: Five themes and 19 subthemes were developed. The DCE was shown to be a value-added position in professional physical therapist programs, whose role and responsibilities are responsive to both internal and external factors to the academy. There is an evolutionary process to the development of a DCE within the academy. A common vision was shared by DCEs and PDs about the future direction of the DCE in today's clinical education marketplace. Discussion: The DCE is a central player in moving academic physical therapist education forward. The patterns of current DCE practice may shed light on plausible reasons for challenges association with the CE atmosphere. Study limitations could include interview bias and bias in analysis. Conclusion: The contemporary role and responsibilities of the DCE were identified, with recommendations for additional studies to enhance the understanding of the DCE in today's academic and clinical environment.